Cardiac asthma or bronchial asthma: a case report - Dewi, Dewa Ayu Rina Wiana; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
Wheezing is often found in patients with asthma bronchiale but wheezing may also be found in paroxysmal nocturnal dyspnea and pulmonary edema (cardiac asthma). Cardiac asthma has been used to explain wheezing and airflow obstruction due to heart failure (HF). The respiratory symptoms such as wheezing, shortness of breath and cough. These symptoms normally occur at night and are common in elderly. Both asthma bronchiale and cardiac asthma are important to diagnose because treatments for asthma bronchiale and HF are different. Here we presented a case report of a 59-years old female diagnosed with cardiac asthma due to heart failure. Cardiac asthma defined as congestive heart failure (CHF) associated with wheezing represents one third of CHF in elderly patients. It is often confused with asthma and exercise-induced bronchospasm. These diseases have different therapies. Cardiac asthma using diuretics and asthma using bronchodilator therapy. CHF can lead to pulmonary congestion and pulmonary edema (PE), and this is classically thought to be the primary cause of cardiac asthma. Current management of cardiac asthma focuses on controlling the underlying HF and PE.